Thinking like a climate : governing a city in times of environmental change - Knox, Hannah, 1977- (Duke University Press, 2020)
"THINKING LIKE A CLIMATE explores how climate change specifically and anthropocenic processes more broadly are affecting human experiences of being in the world. Based on fieldwork in Manchester, England, the birthplace of the Industrial Revolution, Hannah Knox analyzes the ways in which elected officials, activists, and academics are working together to respond to Manchester's climate crisis. The book's central concern is to explore how the material dynamics of climate change that have become known through data, visualizations, and computer models are becoming translated-- or not-- into the mundane work of managing the social order. Ultimately, the project expounds the significance of fighting climate change at the local level and how such a localized change can have a global impact and provide a framework for creating solutions to this problem. The book is divided into two parts that consider the nature and effects of thinking like a climate for both urban governance and anthropology. Chapters are preceded by interludes that provide a series of imagined dialogues through which Knox maps out the origins, form, and institutional positioning of climate change in the city. Part 1 details what happened when people in Manchester were compelled by the findings of climate science to 'think like a climate,' a term coined by Knox to articulate the question of how to incorporate descriptions of a changing climate that emerge from climate models into governmental practice. It focuses on the techniques and methods through which local climate futures come to be imagined, the difficulties encountered in localizing modeled climatic change, and the implications of these challenges for the development of an appropriate response to climate change. The second half of the book explores how alternative modes of relating to climate are being forged. These objects and techniques are not just pragmatic technical responses to climate science, but operate as figurative devices that help us to reimagine the social in climatological terms"--